Response of babassu coconut shell and açai biochar on soil attributes and gas emission - Meneses, Ana Luisa da Conceição de Sousa; de Sousa, Letícia Maria Gomes; Alves, Alan Teixeira; Silva, Manoel Gustavo Lopes; Cordovil, Hellen Patrícia Lemos; de Souza, Leane Castro; de Souza, Luma Castro; Ferreira, Raphael Leone Cruz; Neto, Cândido Ferreira de Oliveira; de Meneses, Kamila Cunha; Melo, Nilvan Carvalho; Cruz, Flávio José Rodrigues (Seven Editora, 2024)
Biochar from waste produced by pyrolysis benefits soil fertility, increases water and nutrient retention and reduces greenhouse gas emissions, promoting more sustainable agricultural practices. Thus, the objective of this study was to investigate the benefits of biochar produced from babassu and açaí coconut shells on the physical, chemical and biological attributes of the soil, as well as on the mitigation of greenhouse gas emissions. A comprehensive literature review was carried out, exploring articles and books in scientific databases. The results showed that the biochar of babassu coconut shells and açaí have significant impacts on the soil. In terms of soil attributes, an increase in water retention capacity, improvement in soil structure and an increase in the availability of essential nutrients for plants were observed. In addition, there was a reduction in the emission of gases such as carbon dioxide-CO2, methane-CH4 and nitrous oxide-N2O, important greenhouse gases, indicating the potential of biochar in mitigating climate change when incorporated into agricultural practices. DOI:https://doi.org/10.56238/sevened2024.023-008